2011
DOI: 10.1007/s00256-011-1168-5
|View full text |Cite
|
Sign up to set email alerts
|

Proximal iliotibial band syndrome: what is it and where is it?

Abstract: Proximal IT band strain represents a unique injury that should be considered in patients who are female athletes or older overweight women who present with pain and tenderness at the iliac tubercle. Imaging of this entity must include the iliac tubercle, which is often excluded in standard hip MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 12 publications
2
54
0
7
Order By: Relevance
“…Therefore, injury to the ITB will influence the activities of the knee joint. [20][21][22] Additionally, displaced distal femur fractures require anatomic reduction of the articular surface. Multiple authors have shown that articular incongruity leads to poor outcomes, such as posttraumatic arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, injury to the ITB will influence the activities of the knee joint. [20][21][22] Additionally, displaced distal femur fractures require anatomic reduction of the articular surface. Multiple authors have shown that articular incongruity leads to poor outcomes, such as posttraumatic arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Kadınlarda ve özellikle koşucularda olmak üzere sporcularda görülür [17]. İlyak tüberkülün inferior kenarı boyunca iliotibial bantta T2A serilerde hiperintens olarak izlenir.…”
Section: Proksimal İliotibial Bant Friksiyon Sendromuunclassified
“…Thus, it is most common in women because they present with wider pelvic girdle and shorter femur as compared with men, which leads to a greater mechanical overload on the iliotibial band as a stabilizer element during ambulation (9) . Clinically, the discomfort tends to be restricted to the iliac tubercle area, worsening with physical activity.…”
Section: Proximal Iliotibial Band Syndromementioning
confidence: 99%